Relationship of preeclampsia in pregnant mothers with ureum and creatinin levels - Nurhadiah, Nurhadiah; Kamilla, Laila; Triana, Linda; Maretalinia, Maretalinia (ELECTRON (Journal of Science and Technology), 2025)
Preeclampsia is a complication of pregnancy due to increased blood pressure, accompanied by proteinuria and odema. Risk factors include primigravida, multiple pregnancy, extreme age at pregnancy, previous history of preeclampsia, family history, and diseases such as kidney, diabetes mellitus, and hypertension. The purpose of this study was to determine the relationship of preeclampsia with ureum and creatinine levels in pregnant women at RSUD Dr. Rubini Mempawah. This research is descriptive analytic with cross sectional approach. The population was all pregnant women who visited in May-July 2024 at RSUD Dr. Rubini Mempawah, with purposive sampling technique. Examination of ureum using Enzym Method and creatinine with IFCC Method. Of the 65 respondents, high ureum levels were found in 20 people (30.8%), with 7 people having preeclampsia and 13 people not. High creatinine levels were found in 21 people (32.3%), consisting of 11 people with preeclampsia and 10 without preeclampsia. Chi-Square test showed a p value = 0.438 (> 0.05) for ureum, indicating no relationship, so Ha was rejected. While p = 0.003 (<0.05) for creatinine, indicating there is an association, so Ha is accepted. In conclusion, there is no relationship between preeclampsia and ureum levels and there is a relationship between preeclampsia and creatinine levels in pregnant women at RSUD Dr. Rubini Mempawah